RESPON KEDELAI (Glycine max L Merril) SEBAGAI TANAMAN SELA TERHADAP CAMPURAN KOMPOS TKKS DENGAN ABU BOILER DAN LCPKS PADA KEBUN KELAPA SAWIT MENGHASILKAN DI LAHAN GAMBUT - Dwika Jepita; Nelvia ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aimed to study the application of the combination of compost of palm oil empty fruit bunches (POEFB) with boiler ash and oil palm mill liquid waste (LW) of oil palm industry to growth and yield of soybean as intercropping in oil palm plantation that have been produced in the peat land. The research was conducted at oil palm plantation (6 years old) at Kualu Nenas Village, Kampar Regency, Riau Province from August to November 2013. The research used Randomize Complete Block Design (RCBD) consist of seven treatment (A = 1.44 kg compost of POEFB + 144 g boiler ash/plot, B = 1.44 kg compost of POEFB + 288 g boiler ash/plot, C = 1.44 kg compost of POEFB + 432 g boiler ash/plot, D = 1.44 kg compost of POEFB + 8.64 ml LW/plot, E = 1.44 kg compost of POEFB + 144 g boiler ash + 8.64 ml LW/plot, F = 1.44 kg compost of POEFB + 288 g boiler ash + 8.64 ml LW/plot dan G = 1.44 kg compost of POEFB + 432 g boiler ash + 8.64 ml LW/plot) each treatment repeated three times. Parameters observed were plant height, number of prymary branches, number of pods, a percentage of pods pithy, flowering age, dry weight of seed and dry weight of 100 seeds. The result showed that the application of 1.44 kg compost of POEFB + 288 g boiler ash + 8.64 ml LW/plot (F) increase plant height, number of pods, a percentage of pods pithy and dry weight of seed significantly compared with the another treatments, but not significantly with the application of 1.44 kg compost of POEFB + 432 g boiler ash + 8.64 ml LW/plot (G) Key Word : Compost Palm of Bunches, Boiler Ash, Liquid Waste, Peat Land, Soybean